REFORMASI POLITIK HUKUM ATAS KEMERDEKAAN MENYATAKAN PENDAPAT DI MUKA UMUM - Said Abdullah (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
Political law is a legal discipline that are categorized as most young compared with other legal disciplines are more classic, such as legal history, legal philosophy and so forth. But even so it does not mean that politics do not have laws that strategic position of a science, because of the axiology able to unlock the mystery of the law as well as the legal disciplines that have been there before.In a country which adheres to democratic governance system, though, still needed rules of the game through legal forms. Democracy without the rule would lead to anarchy. Freedom without considering the interests of living together may lead to chaos, human rights without human basic obligation can lead to arbitrariness.Keyword :  Politics of Law, Democracy